Influence of omega‐3 fatty acids on Tamoxifen‐induced suppression of rat mammary carcinogenesis. Issue 7 (12th October 2013) - Manni, Andrea; Richie, John P.; Xu, Haifang; Washington, Sharlene; Aliaga, Cesar; Bruggeman, Richard; Cooper, Timothy K.; Prokopczyk, Bogdan; Trushin, Neil; Calcagnotto, Ana; Das, Arunangshu; Liao, Jason; et al.
<x xml:space="preserve">Abstract</x> We report here a detailed time course study of the individual and combined chemopreventive effects of Tamoxifen (Tam) and a high fish oil (FO) diet on multiple histologic parameters of mammary carcinogenesis. Groups of female Sprague‐Dawley rats were injected ip with 1‐methyl‐1‐nitrosourea at 50 days of age and assigned to either a control diet (20% corn oil [CO]) or a FO‐rich diet (10% FO + 10% CO) in the presence and absence of Tam in the diet (0.6 ppm). Rats were sacrificed at weeks 4 (before palpable tumors), 8 and 12 (when ∼90% of control rats had palpable tumors). Our results demonstrate a major effect of Tam in inhibiting the development of early preneoplastic lesions. FO, while having a marginal protective effect of it own, enhanced the antitumor action of Tam on all histologic parameters of carcinogenesis, although the effects of the combination were not statistically different from those of Tam alone. The combination of FO and Tam was the only intervention that induced regression of established preneoplastic lesions. We also found that in contrast to plasma, only target tissue n‐3 fatty acids (FAs) levels correlated with select tissue biomarkers of carcinogenesis whose expression was altered in a manner predictive of a protective effect. Our results demonstrating the potentially superior chemopreventive efficacy of Tam and n‐3FA have important translational implications. Our data also emphasize the importance of local factors in affecting target tissue levels and biologic effects of n‐3FA.